SURVEY SOSIAL EKONOMI DAN PELAYANAN AIR MINUM NON PELANGGAN PDAM DI KECAMATAN KALIWIRO KABUPATEN WONOSOBO - Yunanto, Ary (Performance, 2010)
Economic activities and social survey of drinking water services to customers-households in the District of Wonosobo regency Kaliwiro aims to provide information on household characteristics, water resources and usage, the desire to become a customer PDAM and level of ability to pay, as well as socioeconomic households, especially who have not become a customer of PDAM Kabupaten Wonosobo. Based on the results of the analysis Kaliwiro District 120 respondents, aspects of the desire to become a customer of PDAM and the ability to pay, especially regarding the desire to be customerPDAM, the overall 53% or 64 respondents who said "yes", 12% or 14 respondents said "no", and the remaining 35% or 42 respondents said "do not know. Household socio-economic circumstances of respondents is largely complete primary school (84.14%), most respondents worked as cultivators (68.33%), spending over a month less than Rp 700,000 (98.33%), Average average each month can not save Rp 0 (80.83%) and revenue during the first months of below Rp 700,000 (91.66%). Average number of residents of the respondents during the last three months as many as four people. Average water use by a family / respondent which amounted to 120 respondents was 971.74 liters / day / family. This means that in one day a family spends an average of 972 liters of water. Average water usage for 29152.23 liters / month / family. This means that one find in one month the average family spends as much as 29.152 liters of water. Average level of ability to pay within one month intervals are in USD. 30 000 to Rp. 50 000 with an estimated average of Rp. 40 500. Average customer spending levels in the area of non respondents who considered the potential for development of pipeline taps for USD 358 342. Average income level per month in local communities that are considered potential for development of pipeline taps Rp. 398 375.